Evaluation of the diagnostic value of magnetic resonance imaging combined with ultrasound and mammography for breast cancer using array spatial sensitivity encoding technique - Xia, Yingyi; Ling, Zhiyu; Chen, Hao (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the diagnostic efficacy of magnetic resonance imaging (MRI) combined with ultrasound and mammography for breast cancer (BC) using array spatial sensitivity encoding technique (ASSET).MethodsMRI images are processed using parallel imaging (PI) and ASSET techniques. The signal-to-noise ratio (SNR) of ASSET-diffusion-weighted imaging (DWI) and PI-DWI, as well as the contrast-to-noise ratio (CNR) between lesions and normal breast tissue, were compared. Image quality was also assessed. Using 70 cases of BC as the observation group (OG) and 70 non-BC cases as the control group (CG), the imaging characteristics of MRI, ultrasound, and mammography in both groups were compared. The Accuracy (Acc), Sensitivity (Sen), Specificity (Spe), and consistency of single and combined diagnosis using the three methodologies were evaluated.ResultsRelative to the PI-DWI sequence, the ASSET-DWI sequence demonstrated notably shorter scanning time, higher CNR between lesions and normal breast tissue, better lesion visualization, clearer lesion margins, fewer image artifacts, and higher overall image quality (P < 0.05). In contrast to the CG, patients in the OG exhibited a higher proportion of irregular lesion morphology, non-smooth margins, and uneven enhancement on MRI, as well as a higher proportion of low echoic lesions, unclear boundaries, irregular morphology, irregular margins, posterior echo attenuation, and visible blood flow signals on ultrasound. Additionally, a higher proportion of irregular tumor margins, irregular morphology, spiculated signs, calcifications, and absence of capsule were observed on mammography (P < 0.05). Relative to MRI, ultrasound, and mammography alone, the combined diagnostic method showed significantly higher Acc, Sen, Spe, and Kappa values (P < 0.05).ConclusionThe combined use of MRI, ultrasound, and mammography based on ASSET for BC diagnosis offers significant advantages, providing clinicians with more reliable diagnostic tools.